Efficacy and Safety of Antiepileptic Drugs in the Management of Behavioral Issues in Autism Spectrum Disorders: A Systematic Review and Meta-analysis - Sowmyashree Mayur Kaku; Ananya Varshney; Dhwani Ravi; Ann Maria Moncy (Journal of Psychiatry Spectrum)
Background: Autism spectrum disorder (ASD) is often accompanied by comorbidities such as epilepsy and behavioral problems. The interplay between epilepsy, behavior, and language suggests a potential role for antiepileptic drugs (AEDs) in managing ASD-related behavioral issues. Despite some preliminary studies indicating possible benefits, the evidence remains inconclusive. This systematic review and meta-analysis aimed to evaluate the efficacy and safety of AEDs in managing behavioral issues in individuals with ASD. Methodology: Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, we conducted a comprehensive search across multiple databases (PubMed, Ovid MEDLINE, Cochrane Library, Web of Science, and others) for double-blind, placebo-controlled randomized controlled trials (RCTs) published in English. Inclusion criteria focused on individuals with ASD exhibiting behavioral problems, with or without EEG abnormalities, treated with AEDs. Data extraction and quality assessment were performed by two independent reviewers. The primary outcome was focused on investigating the efficacy of AEDs in improving behavioral symptoms, predominantly irritability, and aggression. We also investigated the safety profiles of the AEDs. Results: Seven RCTs met the inclusion criteria, involving AEDs such as valproate, levetiracetam, and topiramate. Two RCTs were excluded due to incompatible outcome measures. Meta-analysis of the remaining five RCTs showed no significant difference in the reduction of aggression and irritability between AEDs and placebo, with high heterogeneity (I2 = 93%). Sensitivity analysis confirmed the nonsignificance and high heterogeneity (I2 = 87%). Adverse effects commonly reported included insomnia and weight gain. Conclusion: This meta-analysis found no significant benefit of AEDs in managing behavioral symptoms of ASD compared to placebo, consistent with previous findings. The high heterogeneity and methodological limitations highlight the need for more robust and larger-scale studies. Future research should consider the role of electroencephalography abnormalities and standardize outcome measures to better evaluate the potential of AEDs in this population or in a specific subgroup of ASD.